Oil production and conflicts in the Niger Delta Region of Nigeria - Peterside, Zainab Brown; Gambo, Audu Nanven (Social Science Research, 2022)
Nigeria, the sixth largest producer of oil in the world has witnessed years of conflict, and oil production has been at the centre of this conflict in Nigeria’s Niger Delta for over six decades. The main objective of this paper is to establish the nexus between oil production and conflict in the Niger Delta. The study adopted the Ex Post Facto research design using both qualitative and quantitative sources of data. It adopted the frustration-aggression theory in its analysis. Findings reveal that the federal government over the years through various laws and policies accounted for both violent and non-violent responses that trigger conflict in the region, such as the Land Use Decree of 1978 and the Derivation Principle. The paper therefore recommends that government should put in place a policy that reserves certain quota of employment opportunities in the oil industry for the people of the region as this will go a long way in reducing conflict.